Ultrasound imaging of tissue overlying the ischial tuberosity: Does patient position matter?. Issue 4 (November 2019) - Gabison, Sharon; Hayes, Keith; Campbell, Karen E.; Swaine, Jillian M.; Craven, Beverly Catharine
Abstract: Background: Deep Tissue Pressure Injury (DTI) occurs in the tissues underlying the skin that may not have visible signs of skin breakdown and may be detected by ultrasound. The optimal position for ischial region ultrasound image acquisition to facilitate assessment of the tissue proximal to the ischias not been determined. Objective: To evaluate the mean difference in geometric and grey scale measures of tissues overlying the ischial tuberosity (IT) acquired from ultrasound images in supine and lateral recumbent simulated sitting positions from adults with spinal cord impairment (SCI). Methods: Nine individuals (3 acute and 6 chronic) with SCI or disease with neurological level of injury C4-T12 and AIS A-D and who used a wheelchair for mobility were recruited and underwent ultrasound acquisition in the supine and lateral recumbent positions. One participant was imaged twice on a separate day. Three images from the left (n = 8) and right (n = 2) IT were scanned using a 6 – 18 MHz linear ultrasound probe (Acuson S2000) with participants' hips and knees flexed to 90° in both the supine and lateral recumbent positions using a single rater protocol. MATLAB Image Processing Toolbox with a customized script was used to obtain mean and maximal thickness, echogenicity and contrast of skin, subcutaneous tissue and muscle. Wilcoxon Signed Rank Test and Bland Altman analysis was used to determine if there were differences between the two image acquisition positions and to construct limits of agreement. Results: Thickness and contrast measures were similar in the supine and lateral recumbent positions (p > 0.05). Muscle echogenicity was lower in the supine position (p = 0.04). Conclusion: There is agreement in geometric and grey scale measures of tissues over the IT between the supine and lateral recumbent positions with the exception of muscle echogenicity, which was lower in the supine position. Since DTI is thought to originate in the muscle and echogenicity plays in a role in abnormal tissue imaging diagnosis, further studies are recommended to determine the impact of body position on muscle echogenicity prior to being used in prospective studies.